2022
DOI: 10.1017/s0007114522003932
|View full text |Cite
|
Sign up to set email alerts
|

Mindful eating for weight loss in women with obesity: a randomised controlled trial

Abstract: Mindful eating has been linked to improvement in binge eating disorder, but this approach in obesity management has shown conflicting results. Our aim was to assess the effect of mindful eating associated with moderate calorie restriction on weight loss in women with obesity. Metabolic parameters, dietary assessment, eating behavior, depression, anxiety, and stress were also evaluated. A total of 138 women with obesity were randomly assigned to three intervention groups: mindful eating associated with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In a similar study which examined the impact of combining mindful eating education with moderate energy restriction (diet) on weight loss in women with obesity, there was no significant difference in weight loss between them. But the mindful eating group exhibited a greater reduction in uncontrolled eating compared to the diet group, and a similar reduction in emotional eating was observed in both groups, surpassing the diet group (21). Consistent with the literature, mindful eating education and applications may have an effect on problematic eating behaviors mostly emotional eating.…”
Section: Discussionsupporting
confidence: 82%
“…In a similar study which examined the impact of combining mindful eating education with moderate energy restriction (diet) on weight loss in women with obesity, there was no significant difference in weight loss between them. But the mindful eating group exhibited a greater reduction in uncontrolled eating compared to the diet group, and a similar reduction in emotional eating was observed in both groups, surpassing the diet group (21). Consistent with the literature, mindful eating education and applications may have an effect on problematic eating behaviors mostly emotional eating.…”
Section: Discussionsupporting
confidence: 82%
“…One of the strategies included a nutritional intervention with the practice of ME. The results demonstrated that there was weight loss in all groups, but with no statistical difference between them [ 38 ]. Apparently, the association of ME with calorie restriction did not promote significant weight loss and also presented several limitations [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mindful eating approaches, which gained increased interest in recent years, were shown to reduce emotional eating, but thus far, without providing evidence for increasing weight loss. 127,128 In addition, several effective behaviour change techniques implicate increasing cognitive awareness and self-efficacy in weight-loss interventions. Self-monitoring of weight or food intake is firmly associated with sustained weight-loss effects and should therefore be strongly encouraged, 129,130 particularly in a weight-loss maintenance phase, at weekly intervals.…”
Section: Strategies For Successful Communicationmentioning
confidence: 99%
“…However, it is still a matter of research to find effective ways to trigger cognitive awareness in the clinical context. Mindful eating approaches, which gained increased interest in recent years, were shown to reduce emotional eating, but thus far, without providing evidence for increasing weight loss 127,128 . In addition, several effective behaviour change techniques implicate increasing cognitive awareness and self‐efficacy in weight‐loss interventions.…”
Section: Practical Strategies For Weight Management In Type 2 Diabetesmentioning
confidence: 99%